Enhancing Vocabulary Acquisition and Retention: The Role of Spaced Repetition in Language Learning - Saksittanupab, Panyanut (Journal of Modern Learning Development, 2024)
Vocabulary acquisition is crucial in language learning, as retaining a large number of words is essential for learners. One effective technique for boosting vocabulary is spaced repetition. Despite extensive research on its effectiveness in retaining vocabulary in L2 courses over time, its full integration into everyday classrooms remains limited. This study aimed to assess the effectiveness of spaced repetition tasks in enhancing vocabulary acquisition among learners and to evaluate the impact of spaced repetition on the retention of vocabulary. The sample were 30 Thai university learners who were selected by convinient sampling. The research instruments for the data collection were the pre-test, post-test, and the vocabulary spaced-repetition tasks. A paired sample t-test was used to analyz the pre-test and post-test scores, while the vocabulary retention rates were analyzed using the descriptive statistics. Results from a paired sample t-test revealed a significant improvement in vocabulary test scores after the intervention (M=21.93, SD=3.31), compared to before (M=11.57, SD=2.46). Additionally, the results from vocabulary retention tests revealed that, after a 10-day period of utilizing spaced-repetition tasks, learners were able to recall about 79.77 percent of the designated target words. Retention rates remained relatively high, hovering around 79.57 percent after 18 days of practice, but showed a decline to 78.27 percent by the 31st day. Following a 60-day lapse without practice, retention decreased further to approximately 75.27 percent. These findings highlight the effectiveness of spaced repetition in improving both short-term vocabulary acquisition and long-term retention among language learners.